ANALISIS SIYASAH SYAR'IYAH TERHADAP DINAMIKA KEADILAN DAN DUALITAS PENEGAKAN HUKUM DALAM SERIAL ANIME ONE PIECE - Malisa Utami; Arif Sugitanata (STIS Darussalam Bermi, 2024)
This study conducts an in-depth analysis of the representation of justice systems and the duality of law enforcement as depicted in the popular manga and anime series